O auto interesse na obra de Adam Smith: a abordagem moral dos agentes sociais - Santos, Cezar Augusto Pereira dos (2014)
The present dissertation - through bibliographical research grounded mainly in the reading of the Theory of Moral Sentiments and of the Wealth of Nations - investigates the connection between Smith's moral philosophy and his approach regarding to the human principles that govern individual pursuit for improving own life condition. For achieve this goal are analyzed some of the Philosophical bases of the author (Stoics, Hutcheson, Hume) and studied the key concepts present in his two books in order to defend the viewpoint of that the Wealth of Nations is a continuity of the Theory of Moral Sentiments. From among the main lessons learned, from the study of the work of Adam Smith, are of which he cultivated, in his personal life, the qualities that in the TMS he considered defining of an excellent character: sobriety, temperance, fairness and magnanimity; which was through of the concepts of sympathy and the impartial spectator, created and developed in the TMS, that Smith created the concept of the prudent man, to which characterizes the majority of people who live in society; that the prudent man of Adam Smith is much different than homo economicus neoclassic; and, mainly, that the Smithian view of self-love is impregnated of moral connotations, once which goes far beyond mere self-interest for material wealth.